Pengaruh Interaksi Edukatif Terhadap Perilaku Belajar Siswa Pada Pembelajaran Pendidikan Agama Kristen Siswa Kelas XI SMK Negeri 1 Balige Tahun Pembelajaran 2023/2024 - Lastri Menalia Sijabat; Limmarten Simatupang; Baginda Sitompul; Dorlan Naibaho; Goklas J. Manalu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The aim of this research is to find out how much influence educational interactions have on student learning behavior in Christian Religious Education learning for class Christian Religious Education for class XI students at SMK Negeri 1 Balige for the 2023/2024 academic year. With a population of all class Data was collected using a closed questionnaire with 46 items compiled by the author based on variable indicators according to expert theory. The questionnaire trial was carried out on 30 respondents of class Y 0.321 – 0.637 (there are 2 question items that have validity less than r table = 0.361, namely item number 33 and 41 so that the invalid questionnaire is discarded. Thus, the valid questionnaire is 44 questions. And the reliability of the questionnaire trial is variable X which is at a value of 0.829 it is in a very strong interpretation, and the reliability of the questionnaire trial of variable Y which is at a value of 0.842 and is in a very strong interpretation and has been tested for validity and reliability. The results of data analysis show that there is a positive and significant influence between Educational Interaction on Learning Behavior Students in Christian Religious Education Learning for Class XI Students at SMK Negeri 1 Balige for the 2023/2024 Academic Year. By testing the relationship, it is obtained that rcount>rttable is 0.524>0.297, with a significant relationship test tcount>ttable is 4.257>2.000, the coefficient of determination is 27.5%. This means that H0 is rejected and Ha is accepted. This research suggests to teachers to always improve educational interactions in learning, so that the learning behavior of Class